2021
DOI: 10.1021/acs.langmuir.1c00235
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Acoustic Energy Absorption in Confined Aqueous Solutions by PNIPAM Microgels: Effects of Bulk Viscosity

Abstract: Ultrasound propagation in liquids is highly influenced by its attenuation due to viscous damping. The dissipated energy will be partially absorbed by the liquid due to its dynamic viscosity as well as its bulk viscosity. The former results in the generation of a flow that is called acoustic streaming, and the latter is associated with the vibrational and rotational relaxation of liquid molecules. Measuring the ultrasonic wave attenuation due to the bulk viscosity is presented as a novel method in this article.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
0
12
0
1
Order By: Relevance
“…This is due to intermolecular aggregation caused by the LCST effect, which depends on the polymer concentration. Beyond LCST, there is a higher phase separation that is unstable as temperature increases [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is due to intermolecular aggregation caused by the LCST effect, which depends on the polymer concentration. Beyond LCST, there is a higher phase separation that is unstable as temperature increases [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…The kinetics of the energy absorption has been quantified similarly to our previous work [ 15 ] using image processing and the absorbed energy over time for different solution concentrations (i.e., 0.2, 1, and 5 wt%) is shown in Figure 2 . Increasing the solution concentration increases the ultrasound energy absorption and consequently increases the speed of turbidity evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the solution concentration increases the ultrasound energy absorption and consequently increases the speed of turbidity evolution. In our previous work [ 15 ], it is shown that increasing the solution concentration leads to a greater increase in “bulk viscosity” that reflects the vibrational and rotational degrees of molecular freedom in comparison with the increase in “shear viscosity” that corresponds to their translational movement. Therefore, in denser solutions, the PNIPAM chains are slower in the structural reorganization of their molecules upon ultrasonic actuation and thus the energy absorption is larger.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations